Development of work based learning models in education of vocational midwifery: part of need analysis - Marlina, Hastuti; Jalinus, Nizwardi; Rizal, Fahmi (Universitas Negeri Padang, 2020)
Skills in the world of work become demands that must be fulfilled by every education practitioner. Vocational education graduates produced by tertiary institutions do not have maximum competencies that are ready to be used for work, so there is often a gap between the competencies desired by graduates and the competencies produced by the education world. Educational literacy is needed to overcome this gap, one of them is by developing work-based learning models in midwifery vocational education. This study aims to analyze the needs of midwifery graduates, midwifery graduates 'recognition and midwifery lecturers' views on the general competency aspects of midwife graduates and work skills. This study involved five obstetricians from various institutions, five graduates working in various health institutions and five lecturers from various midwifery institutions. The results of the needs analysis showed that the low evaluation of midwifery users regarding the aspects of general competence and work skills of midwives in one year of work, so that the development of work-based learning models in midwifery education is very necessary to equate the desires of graduate users with the graduates produced. Furthermore, the resulting model will be tested effectively, valid and practical so that graduates can compete in the world of work.